Analisis Efektivitas Jalur Antrian Pada Sistem Transaksi PT. Pos Indonesia Di Tenggarong - Juwita, Intan; Iskandar, Iskandar; Ilham, Ilham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The purpose of this study was to determine the effectiveness of the application of the queuing system at the payment counter at PT. Pos Indonesia Tenggarong Branch. In this study, the analysis of the multiple line queuing system (M/M/S) was used. The problem that exists in this study is the fact that the queue conditions at the payment counter at PT. Pos Indonesia Tenggarong Branch at 08.30-10.30 is quite busy and at 11.30-12.30 it is not busy, so the application of a queuing system is very necessary to obtain an efficient number of teller services. The results of the analysis with two service servers, the time spent by a consumer in the system (Ws) the fastest is 1.39 minutes and the longest is 4.62 minutes. Meanwhile, by using three service servers, the time spent by a consumer in the fastest (Ws) system is 1.07 minutes and the longest is 3.51 minutes compared to the standard time of the post office company for 4 minutes of service. Operations become larger, with the addition of one service teller to three service tellers at the Post Office, it is declared ineffective because the Post Office must add service fees, while the number of people queuing in the system is still in the range of 1 or people queuing in the system and the time difference service is only 30 seconds to 1 minute apart.